Semiotic Analysis of Gender Inequality Representation in the 2023 Movie Gadis Kretek - Salam, Fikri (Universitas Musamus Merauke, 2024)
This research discusses the gender gap in the movie Gadis Kretek episode 1 where women are implied as second divine beings. In this study, the character Jeng Yah experiences this discrimination. This research methodology uses descriptive qualitative research method using Charles S. Pierce semiotic analysis and gender approach. The text features three scenes depicting a woman's struggle in public, lack of confidence in public, and a caged bird. The first scene shows a woman smoking at a banquet, and the second scene shows a closed blue door, emphasizing restraint and limitation. The third scene depicts a bird in a cage, symbolizing powerlessness and cultural limitations. This article analyses the film Gadis Kretek using semiotic analysis and gender and feminist analysis. It shows how cigarettes are associated with men and masculinity, and how women are discriminated against in the public sphere. The film encourages women to think of themselves as secondary and shows how sexism prevents women from achieving them.